Automaticity in translation: Effects of time pressure and work experience - Weng, Yu; Zheng, Binghan (Meta, 2024)
Automaticity is a key construct in skill acquisition. This study explored how time pressure and work experience affect the degree of translation automaticity in novice (N = 35) and experienced translators (N = 30) using eye-tracking and keystroke-logging metrics. Four aspects of automaticity in translation were examined, namely, processing speed, degree of parallel processing, effort taken to produce each production unit and attention allocation pattern to the source/target text areas. Results showed that time pressure rendered more automatic translation at the micro-level as evidenced by increased speed, deeper parallel processing and less effort (measured by time) required for each production unit. Translators’ professional experience affected automaticity at the macro-level since experienced translators displayed a significantly more automatic comprehension process as compared to novices. In conclusion, whilst time pressure enhances automaticity in certain translation behaviours, the most fundamental factor for automaticity development in translation skills is experience. The findings could provide implications for translation practice and training.